The Old Testament Pseudepigrapha ; v. 1 - Charlesworth, James H. (New York, NY Doubleday, 1983)
Contents : v. 1 : Apocalyptic literature and testaments. Includes bibliographical references and index.
Keywords: Apocryphal books (Old Testament) -- criticism, interpretation, etc